Variation in histopathological assessment and association with surgical quality indicators following oesophagectomy. Issue 1 (28th December 2020) - Pucher, P H; Green, M; Bateman, A C; Underwood, T J; Maynard, N; Allum, W H; Novelli, M; Gossage, J A; ,
Abstract: Background: Histopathological outcomes, such as lymph node yield and margin positivity, are used to benchmark and assess surgical centre quality, and are reported annually by the National Oesophago-Gastric Cancer Audit (NOGCA) in England and Wales. The variation in pathological specimen assessment and how this affects these outcomes is not known. Methods: A survey of practice was circulated to all tertiary oesophagogastric cancer centres across England and Wales. Questions captured demographic data, and information on how specimens were prepared and analysed. National performance data were retrieved from the NOGCA. Survey results were compared for tertiles of lymph node yield, and circumferential and longitudinal margins. Results: Survey responses were received from 32 of 37 units (86 per cent response rate), accounting for 93.1 per cent of the total oesophagectomy volume in England and Wales. Only 5 of 32 units met or exceeded current guidelines on specimen preparation according to the Royal College of Pathologists guidelines. There was wide variation in how centres defined positive (R1) margins, and how margins and lymph nodes were assessed. Centres with the highest nodal yield were more likely to use systematic fat blocking, and to re-examine specimens when the initial load was low. Systematic blocking of lesser curve fat resulted in significantly higher rates of patients with at least 15 lymph nodes examined (91.4 versus 86.5 per cent; P = 0.027). Conclusion: Preparation and histopathological assessment of specimens varies significantly across institutions. This challenges the validity of currently used surgical quality metrics for oesophageal and other tumours. Abstract : Histopathological outcomes, such as nodal count or margin positivity rates, are used for surgical quality assessment and national benchmarking. This national UK survey of practice reported the variance in pathological specimen assessment and its effect on these outcomes. In the absence of standardized assessment and reporting, current metrics may not be valid.